Experimental and theoretical studies on the pressure fluctuation of an internal gear pump with a high pressure. (February 2019) - Liu, Ying-Yuan; Li, Yi-Ran; Wang, Le-Qin
In this paper, the flow ripple equation is derived to analyze the effect of working condition on pressure pulsations of an internal gear pump. Results indicate that working pressure has a significant effect on pressure fluctuation of the internal gear pump, while the rotating speed has a complex influence on the pressure pulsation behavior. Then, pressure pulsations of the internal gear pump under different working conditions are discussed by experimental investigations. Results show that the internal gear pump taken for analysis has a low-pressure pulsation at a high working pressure and a relatively high rotational speed. Regarding the frequency spectrum of the pressure pulsation, the dominant frequency is Z * f n, i.e. the product of the tooth number of the driving gear (gear shaft) and its rotational frequency for many working conditions, caused by the inevitable unsteady discharge process of gear pumps. It transforms to the rotational frequency of the gear shaft ( f n ) for a high rotational speed or a high operating pressure, but to the rotating frequency of the internal gear ring (2/3 f n ) only for a high operating pressure. The occurrence of the two frequencies (2/3 f n and f n ) may result from the deformation of the gear ring and the gear shaft under the unbalanced radial forces caused by a high working pressure. Moreover, the frequency spectrum of the inlet pressure pulsation presents some differences from that of the outlet pressure pulsation. This is because the inlet pressure may be influenced by cavity generated at the suction side of the pump.